Crosstalk Between GABAergic Neurotransmission and Inflammatory Cascades in the Post-ischemic Brain: Relevance for Stroke Recovery - Michalettos, Georgios; Ruscher, Karsten (Frontiers in Cellular Neuroscience, 2022)
Adaptive plasticity processes are required involving neurons as well as non-neuronal cells to recover lost brain functions after an ischemic stroke. Recent studies show that gamma-Aminobutyric acid (GABA) has profound effects on glial and immune cell functions in addition to its inhibitory actions on neuronal circuits in the post-ischemic brain. Here, we provide an overview of how GABAergic neurotransmission changes during the first weeks after stroke and how GABA affects functions of astroglial and microglial cells as well as peripheral immune cell populations accumulating in the ischemic territory and brain regions remote to the lesion. Moreover, we will summarize recent studies providing data on the immunomodulatory actions of GABA of relevance for stroke recovery. Interestingly, the activation of GABA receptors on immune cells exerts a downregulation of detrimental anti-inflammatory cascades. Conversely, we will discuss studies addressing how specific inflammatory cascades affect GABAergic neurotransmission on the level of GABA receptor composition, GABA synthesis, and release. In particular, the chemokines CXCR4 and CX3CR1 pathways have been demonstrated to modulate receptor composition and synthesis. Together, the actual view on the interactions between GABAergic neurotransmission and inflammatory cascades points towards a specific crosstalk in the post-ischemic brain. Similar to what has been shown in experimental models, specific therapeutic modulation of GABAergic neurotransmission and inflammatory pathways may synergistically promote neuronal plasticity to enhance stroke recovery.